Loyalty among academics at UiTM Terengganu: application of logistic regression / Nor Aini Hassanuddin ... [et al.] - Hassanuddin, Nor Aini; Mat Zin, Sakinah; Yusoff, Rohana; Awang, Yunita (2012)
Factors that determine loyalty among academics at UiTM Terengganu were looked into. This study was conducted on 202 lecturers at UiTM Terengganu who have served for at least one semester. Descriptive analysis was used to gauge the overall picture of factors influencing academics’ loyalty. Logistic regression was applied to look at the relationship between variables. Evidence showed that field, management-lecturer relationship and SKT satisfaction factors contributed towards loyalty. Findings of this study will provide insight for management to evaluate the university climate in improving the learning environment and elevating the productivity of the university.